Plasma proteomic analysis of zebrafish following spring viremia of carp virus infection. Issue 86 (March 2019) - Medina-Gali, Regla; Belló-Pérez, Melissa; Ciordia, Sergio; Mena, María Carmen; Coll, Julio; Novoa, Beatriz; Ortega-Villaizán, María del Mar; Perez, Luis
Abstract: To better understand spring viremia of carp virus (SVCV) pathogenesis in zebrafish proteomic analysis was used to examine the plasma protein profile in SVCV-infected zebrafish. A total of 3062 proteins were identified. Of those 137, 63 and 31 proteins were enriched in blood samples harvested at 1, 2 and 5 days post SVCV infection, respectively. These altered host proteins were classified based on their biological function: 23 proteins under the response to stimulus term were identified. Interestingly, at the top of the up-regulated proteins during SVCV infection were the proteins of the vitellogenin family (Vtg) and the grass carp reovirus-induced gene (Gig) proteins. Real-time RT-PCR evaluation of samples from internal organs verified that SVCV infection induced vtg and gig2 gene expression already at day 1 post-infection. Western blot analysis revealed the presence of Vtg protein only in blood of SVCV-infected fish. This is the first proteomic study to reveal the involvement of Vtg proteins in adult fish response to viral challenge. It also highlights the role of Gig proteins as important factors in antiviral response in fish. This work provides valuable relevant insight into virus-host interaction and the identification of molecular markers of fish response to virus. Graphical abstract: Image 1 Highlights: First proteomic analysis of blood samples from virus-infected zebrafish. The number of up-regulated plasma proteins in SVCV-infected samples increased rapidly and dropped after 1 dpi. Vitellogenins and Gig2 proteins were the most up-regulated plasma proteins after SVCV infection of zebrafish. Vitellogenins are novel biomarkers of viral infections in fish.